Representations of the territory. A vision from the peasant and indigenous youth of the Group for the Defense of Land and Territory of the department of Cordoba - Arias, Lina Marcela (Facultad de Ciencias Políticas y Sociales, 2020)
This research exercise is an analysis of the rural youths’ and young peoples’ representations constructed regarding their territory. It shows how these representations reveal responses referred to rooting or uprooting in their territory. It is an investigation that contributes to the recognition of the representations of territory by a sector of the population unseen by society, such as rural youth, in this case, specifically the Colombian rural youth. The elements that were taken as references to develop these representations are associated with rooting and uprooting, daily life and the space where young people live together, the perception of life and of access to rights, social, cultural and economic transformations in the territory and the expectations of young people, as well as the dilemma of staying or leaving their territories.